Association of preoperative blood biomarkers with postoperative major adverse cardiac events and mortality in major orthopaedic surgery: a systematic review and meta-analysis - Lin Lu; Yi Ren; Zhen Hua; Yanxia Sun; Zhenghao Wen; Suzhen Zhou (BMJ Open)
Objective The association between preoperative blood biomarkers and major adverse cardiac events (MACEs) as well as mortality after major orthopaedic surgery remains unclear. This study aimed to assess the association between preoperative blood biomarkers and postoperative MACEs as well as all-cause mortality in patients undergoing major orthopaedic surgery.Design A systematic review and meta-analysis.Data sources PubMed, EMBASE, the Cochrane Controlled Trials Register and Cochrane Database of Systematic Reviews from inception to 20 October 2024 were searched.Eligibility criteria Observational or experimental studies reporting the correlation between preoperative blood biomarkers and postoperative MACEs—categorised as short-term (within 3 months) or long-term (beyond 3 months)—and all-cause mortality in patients undergoing major orthopaedic surgery.Data extraction and synthesis Data from studies reporting OR or HR and its 95% CI were pooled for analysis using random-effects model.Results 21 preoperative blood-based biomarkers from 80 studies with 226 468 patients were analysed. Elevated preoperative cardiac biomarkers were correlated with a heightened risk of MACEs within 3 months (natriuretic peptide: OR 3.37, 95% CI 2.07 to 5.47, I2=87.9%; cardiac troponin: OR 4.89, 95% CI 1.52 to 15.75, I2=69.5%) with significant heterogeneity. Only natriuretic peptide was associated with a high-risk long-term MACEs (>3 months) (OR 3.52, 95% CI 1.73 to 7.17, I2=86.2%). In contrast, cardiac biomarkers were not identified as having prognostic value for all-cause mortality in this patient cohort. Additionally, an increased risk of all-cause mortality was associated with preoperative abnormal levels of albumin (OR 1.15, 95% CI 1.06 to 1.24, I2=84.8%), creatinine (OR 1.54, 95% CI 1.12 to 1.95, I2=0), 25(OH)D (OR 1.58, 95% CI 1.01 to 2.14, I2=0) and glomerular filtration rate (GFR) (OR 1.12, 95% CI 1.06 to 1.17, I2=0), rather than cardiac biomarkers.Conclusions The study proposed that cardiac biomarkers assessed before surgery could offer prognostic insight into short-term MACEs, while preoperative abnormal levels of albumin, creatinine, 25 (OH)D and GFR might be prognostic valuable for all-cause mortality following major orthopaedic surgery.PROSPERO registration number CRD42022352091.